Improving Food Safety and Food Quality: The Case of Nestle - Ern Yee Chung; Daisy Mui Hung Kee; Jia Wei Chan; Sian Yun Tiong; Yuan Wen Choke; Jun Shern Low; Dalal Al Ajmi; Hanisha Motwani (AIBPM Publisher, 2020)
Food safety and food quality are important issues in the food industry. The food manufacturers are responsible to provide a high quality, clean and safe food to consumers. Mismanaging food safety and food quality may potentially lose the food’s nutritional value and bring harm to consumers’ health and put the food manufacturers’ reputation at risk. Nestle is one of the world largest food and beverage companies located in 190 countries and offers more than 2,000 brands to their customers. One of the many reasons behind the success of Nestle is their strong leadership, with their vision and strategies, making a long-term commitment to the health and well-being of their customers. Nestle constantly identifies ways to improve the nutritional profile of their foods and ensure the food safety and food quality are their top priority concern. The paper presents the factors affecting food safety and food quality in Nestle. The paper also discusses how Nestle improves the food safety and food quality.